Zebrafish Comparative Genomics and the Origins of Vertebrate Chromosomes - Postlethwait, John H.; Woods, Ian G.; Ngo-Hazelett, Phuong; Yan, Yi-Lin; Kelly, Peter D.; Chu, Felicia; Huang, Hui; Hill-Force, Alicia; Talbot, William S. (Genome Research, 2000)
To help understand mechanisms of vertebrate genome evolution, we have compared zebrafish and tetrapod gene maps. It has been suggested that translocations are fixed more frequently than inversions in mammals. Gene maps showed that blocks of conserved syntenies between zebrafish and humans were large, but gene orders were frequently inverted and transposed. This shows that intrachromosomal rearrangements have been fixed more frequently than translocations. Duplicated chromosome segments suggest that a genome duplication occurred in ray-fin phylogeny, and comparative studies suggest that this event happened deep in the ancestry of teleost fish. Consideration of duplicate chromosome segments shows that at least 20% of duplicated gene pairs may be retained from this event. Despite genome duplication, zebrafish and humans have about the same number of chromosomes, and zebrafish chromosomes are mosaically orthologous to several human chromosomes. Is this because of an excess of chromosome fissions in the human lineage or an excess of chromosome fusions in the zebrafish lineage? Comparative analysis suggests that an excess of chromosome fissions in the tetrapod lineage may account for chromosome numbers and provides histories for several human chromosomes.
10.1101/gr.164800